Mirroring application or plastic reformulation of plasticity? (KULT_online, 2015)
Philosopher Catherine Malabou’s elaboration of plasticity has taken several forms: from her materialist synthesis of dialectics and deconstruction, through reading neurosciences via a critique of the limits of psychoanalysis, to her engagement with Heidegger, Marx, Levinas, Nietzsche, or her take on feminism and sexual difference, as well as her critique of biopolitics. Plastic Materialities contributes to this formative process by bringing together three previously unpublished essays as well as the extension and critique of her work by scholars in the fields of law, political theory, psychoanalysis, biology, art, and literature.